Implementation of Islamic Business Values in the Management of Coffee Shop Business in Banda Aceh - Rasyada, Tiara; Edba, Dauria; Maulina, Dinda; Halim, Hendra (Universitas Syiah Kuala, 2025)
This research analyzes the implementation of Islamic business values in the management of coffee shops in Banda Aceh, a city with strong implementation of Islamic Sharia in various aspects of life. Using a qualitative approach with a literature study method, this research explores the manifestation of Islamic business values in four main dimensions: spiritual (tawhid), business ethics ('is), social (ihsan), and operational (khalifah). Data collection was conducted through a systematic search of scientific literature related to Islamic economics, sharia business management, and the development of coffee shops in Aceh published in the 2020-2024 timeframe. The results showed that although most coffee shop managers in Banda Aceh have a good understanding of the principles of Islamic economics, their implementation has not been fully integrated in all aspects of business management. The most consistently applied practices are the provision of halal products (100%) and worship facilities (93%), while aspects of sharia financial management (35%) and sharia-based HR management systems (56%) still face implementation challenges. The motivation of managers in implementing Islamic values also varies, with coffee shops managed based on religious awareness showing higher consistency of implementation. This research contributes to the development of a coffee shop business management model that integrates Islamic values comprehensively and adaptively to the modern context, and highlights the importance of strengthening regulations and support from various stakeholders to create a sustainable sharia-based business ecosystem.